Preliminary study on the physical properties of palm ash and PCB waste mixed with phenolic resin. - Mohd Radzi, Ali; Shamsul Baharin, Jamaludin, Prof. Dr.; Che Mohd. Ruzaidi, Ghazali, Prof. Madya; Nur Hidayah, Ahmad Zaidi; Alida, Abdullah (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.